Alvenaria armada de tijolo vazado de barro - pilares curtos - Grilo, Marcos Barbosa (1978)
Starts a research line on reinforced air brick masonry, to study objetive the conduct of these structures under compression, at service limit and ultimate limit states. Fifteen columns of square section, built with air bricks usually used in constructions, were tested until the rupture point. The quantity and the category of reinforcing bars were used as parameters for variation. The analysis of the results were done using comparative diagrams and tables of these structures at service, at the first limit state and near the rupture point. The masonry and reinforcing bars characteristics and design diagrams and the axial compression verification formula were completely defined.